SOSIALISASI MEMBANGUN KARAKTER DAN ETIKA CALON PENDIDIK MAHASISWA UNIVERSITAS BINA BANGSA - Rahmadani, Kurniati; Umalihayati, Umalihayati; Fricticarani, Ade (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Teacher is a forefront profession of change and improvement for future generations. The teacher is a role model for students and the community. Socialization activities provide reinforcement of Character Building and Ethics for prospective educators and one of the steps that must be taken to create professional teaching staff. By doing so, all students are expected to obey and comply with the educator's code of ethics, educator ethics, as well as an overview of how to behave and act as an educator so the Indonesian national identity with character will always be in the soul of next generation